LA INCIDENCIA DE LOS PROCESOS DE DESARROLLO EN LA CREACIÓN DE LA FONOLOGÍA DE UNA SEGUNDA LENGUA - Pavón Vázquez, Víctor (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Studies on the processes that shape the learning/acquisition of a second language phonology mainly deal with defining the nature of transfer processes and internal developmental processes and clarifying the roles played by these two different influences. There seems to be disagreement with respect to the importance that should be given to each of these processes. In our opinion, any research to be carried out in this field must take into account the learner’s new phonological system, particularly in terms of the existence of clear systematic and structured characteristics. If attention is paid to the nature of the regular properties of interlanguage (IL) phonology, it should be possible to analyze more accurately the influence of the mother tongue (L1), the target language (L2) and the learner’s own systematic phonological development. It is our intention, then, to point out the need to study the sometimes neglected, internal developmental processes in the explanation of how interlanguage phonology is created.